2017
DOI: 10.1084/jem.20170468
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation promotes activation-induced cytidine deaminase activity at the Myc oncogene

Abstract: The molecular mechanisms that regulate AID mutator activity at off-target genes are not well characterized. Mu et al. show AID phosphorylation dynamically controls activity at Myc and other sites. Pharmacological induction of AID phosphorylation leads to increased mutations, double strand breakss and translocations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Since AID activity at Myc is limiting in translocation generation, 7 this assay also served as a proxy for measuring off-target activity and indicated that preventing phosphorylation did not impact AID off-target base-line activity. Further, global DSB formation, measured by analyzing the frequency of γH2AX focus formation, was not appreciably decreased in AID-S38A B cells relative to WT cells 6 . These results implied that under non-pathologic conditions AID is minimally phosphorylated at off-target sites.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Since AID activity at Myc is limiting in translocation generation, 7 this assay also served as a proxy for measuring off-target activity and indicated that preventing phosphorylation did not impact AID off-target base-line activity. Further, global DSB formation, measured by analyzing the frequency of γH2AX focus formation, was not appreciably decreased in AID-S38A B cells relative to WT cells 6 . These results implied that under non-pathologic conditions AID is minimally phosphorylated at off-target sites.…”
mentioning
confidence: 78%
“…Our most recent study assessed the role of AID-pS38 in generating oncogenic Myc translocations. We found that the AID-S38A substitution did not decrease generation of Myc/Igh translocations during normal CSR 6 . Since AID activity at Myc is limiting in translocation generation, 7 this assay also served as a proxy for measuring off-target activity and indicated that preventing phosphorylation did not impact AID off-target base-line activity.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Naïve B cells were purified from spleens of wild-type and Wwox KO 16–17 day-old mice (38, 39) by anti-CD43 bead depletion (Miltenyi Biotec). Cells were cultured in LPS (25 μg/ml, Sigma-Aldrich) and IL-4 (5 ng/ml, RD) for 72 h. To determine CSR to IgG1, cultured B cells were stained with anti-IgG1 antibodies and flow cytometric analysis of surface Ig expression was performed on a LSRFortessa (BD) with scatter gating and propidium iodide staining to exclude dead cells (40). Results were analyzed with FlowJo (Tree Star) and averages were obtained from triplicate cultures of six individual spleens in four independent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…AID mis-expression induces genome instability and cancer [ 59 ]. Within B cells, deregulation of AID protein levels [ 60 , 61 ] or post-translational modifications that control activity [ 62 , 63 ] result in genome instability and chromosome translocations. Therefore, viral factors that induce AID and RAG1/2 or disrupt the regulatory mechanism of these proteins could produce oncogenic lesions that contribute to associated lymphomas.…”
Section: Germinal Center Processes That Shape B Cell Evolution Andmentioning
confidence: 99%